2004
DOI: 10.1074/jbc.m309070200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of [Ca2+] Signaling Dynamics and Metabolism by Perinuclear Mitochondria in Mouse Parotid Acinar Cells

Abstract: [Ca 2ϩ ] i signals may be tuned to evoke specific physiological responses in these cells. The major function of pancreatic acinar cells is the exocytosis of zymogen granules that can be activated by apically confined [Ca 2ϩ ] i signals (6), suggested to be the major physiological [Ca 2ϩ ] i signal evoked by threshold agonist concentrations (7). These apically confined [Ca 2ϩ ] i signals are in part because of the distribution of mitochondria, which form a belt around the apically located zymogen granules (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 58 publications
3
52
3
1
Order By: Relevance
“…Moreover, the onset of the increase in [Ca 2+ ] N did not differ from that in [Ca 2+ ] S within the sampling interval of our recordings (33 ms). In contrast to our study, a significant delay (∼300 ms) was observed in carbachol-stimulated parotid acinar cells [33]. In these cells, the majority of mitochondria are localized around the nucleus and it was found that inhibitors of mitochondrial Ca 2+ uptake abolished this delay suggesting the involvement of these organelles in propagation of the Ca 2+ signal from the cytosol into the nucleus.…”
Section: A 3-d Model For Amplitude Modulation Of Nuclear Ca 2+ Signalscontrasting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the onset of the increase in [Ca 2+ ] N did not differ from that in [Ca 2+ ] S within the sampling interval of our recordings (33 ms). In contrast to our study, a significant delay (∼300 ms) was observed in carbachol-stimulated parotid acinar cells [33]. In these cells, the majority of mitochondria are localized around the nucleus and it was found that inhibitors of mitochondrial Ca 2+ uptake abolished this delay suggesting the involvement of these organelles in propagation of the Ca 2+ signal from the cytosol into the nucleus.…”
Section: A 3-d Model For Amplitude Modulation Of Nuclear Ca 2+ Signalscontrasting
confidence: 54%
“…Because strategically localized mitochondria have dramatic effects on the propagation of intracellular Ca 2+ signals [32,33], we determined their subcellular localization by expressing a mitochondria-targeted variant of yellow fluorescent protein (COX8-EYFP) using a transfection method described previously [34]. Fig.…”
Section: Three-dimensional Model For Amplitude Modulation Of Nuclear mentioning
confidence: 99%
“…However, the discrepancy in the size of the initial [Ca 2+ ] M peak may also be due to the high affinity of the dye. In fact, the lower affinity dye rhod-FF (Kd = 19 M) has been used in some cases to avoid saturation with Ca 2+ or to minimize the signal coming from mistargeted cytosolic dye [17,18]. In these papers, although the data were not calibrated in [Ca 2+ ] values, it was actually shown that rhod-2 saturated with Ca 2+ in mitochondria during cell stimulation, while rhod-FF had a better response.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous types of differentiated cells have also been reported to exhibit perinuclear arrangements of mitochondria, including fibroblasts (Yaffe, 1999), pancreatic ascinar cells (Johnson et al, 2003;Bruce et al, 2004), and astrocytes and neurons (Collins et al, 2002). The addition of ES and adult stem cells to this list reopens the question "Is there a benefit for some cells having a perinuclear arrangement of mitochondria in comparison to cell types that do not?"…”
Section: The Significance Of Perinuclear Arrangement Of Mitochondriamentioning
confidence: 99%